Comparing the physiques of elite Polish female and male swimmers training for short and long distances with their non-training peers – Is swimming a health-promoting sport? - Aleksandra Stachowicz; Anna Kęska; Katarzyna Milde; Małgorzata Stachowicz (PLoS ONE, 2025)
In athletes, anthropometric measures are widely used to prescribe desirable body weight, to optimize competitive performance, and to evaluate the effectiveness of various training regimens. However, it also seems interesting to find out which values of anthropometric indices showing a significant relationship with health risk characterise the top athletes, especially in popular sports. The aim of the study was to characterise the physique of female and male swimmers compared to their non-training peers and to determine to what extent it is influenced by training distance. Somatic measurements were taken in 30 female and 30 male top Polish swimmers. The subjects were divided into four groups, i.e., SDF (n = 24) and SDM (n = 24) groups comprising females and males training for short-distance, and LDF (n = 6) and LDM (n = 6) groups comprising those training for long-distance. The swimmers were compared with their non-training peers, 373 females and 155 males aged 20–30 years. BMI, WHR, BF, BAI and Slenderness index were calculated to describe the athletes’ physiques. Swimmers had significantly lower BMI (19.3 ± 1.4 in SDF and 22.1 ± 0.6 in LDF compared to 23.1 ± 3.7 in non-swimmers, p < 0.001) and WHR (0.7 ± 0.0 in SDF and 0.8 ± 0.0 in LDF, compared to 0.9 ± 0.1 in non-training peers, p < 0.001) and BF, but only in SDF group (22.7 ± 1.6, compared to 24.2 ± 5.9 in non-swimmers, p < 0.01). In contrast, athletes had significantly higher Slenderness index values (44.8 ± 1.1 in SDF, and 42.9 ± 0.5 in LDF, vs. 41.9 ± 3.6 in non-training peers, p < 0.001). It was also found that the distance trained differentiates especially the physique of female swimmers, and that physique has a greater impact on athletic performance in short-distance swimmers. Monitoring the physique of top swimmers provides an insight into the type of adaptation to the training process, which in turn enables the identification of factors that determine sports success. Such observations also document the health benefits of swimming, allowing this form of physical activity to be promoted to the public.